Reactivity of Dialumane and "Dialumene" Compounds toward Alkenes. Issue 36 (18th July 2013) - Zhao, Yanxia; Lei, Yibo; Dong, Qingsong; Wu, Biao; Yang, Xiao‐Juan
Abstract The reactions of dialumane [L(thf)AlAl(thf)L] (1, L=[(2, 6‐iPr2C6H3)NC(Me)2]2−) with stilbene and styrene afforded the oxidation/insertion products [L(thf)Al(CH(Ph)CH(Ph))AlL] (2) and [L(thf)Al(CH(Ph)CH2)Al(thf)L] (3), respectively. In the presence of Na metal, precursor 1 reacted with butadienes, possibly through the reduced "dialumene" or the "carbene‐like" :AlL species, to yield aluminacyclopentenes [LAl(CH2C(Me)C(Me)CH2)Na]n (4 a) and [Na(dme)3][LAl(CH2C(Me)CHCH2)] (4 b, dme=dimethoxyethane) as [1+4] cycloaddition products, as well as the [2+4] cycloaddition product 1, 6‐dialumina‐3, 8‐cyclodecadiene, [Na(dme)2][LAl(CH2C(Me)C(Me)CH2)2AlL] (5). The possible mechanisms of the cycloaddition reactions were studied by using DFT computations.